Peningkatan Nilai Produk pada Usaha Keripik Babang di Desa Pudak Kabupaten Muaro Jambi - Mustika, Candra; Achmad, Erni; Nurhayani; Nurjanah, Rahmah; Pirhanto, Purwaka Hari (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The Babang Chip Business is a home-based business located in Pudak Village. This business continues to grow, but faces obstacles because it does not yet have a PIRT license and Halal Certificate as requirements for legality and product quality assurance. The purpose of this community service is to increase product value through assistance with licensing and halal certification so that the business has legal legitimacy and is able to expand its market. The implementation of these legal requirements is expected to increase consumer confidence, strengthen competitiveness, and open up broader marketing opportunities. After the community service was carried out, the PIRT and Halal Certificate application process has been completed and is awaiting official issuance. The partners felt greatly assisted by the administrative assistance provided because it facilitated access to the digital licensing system. The methods used were lectures, discussions, and direct assistance so that the partners could be active during the community service process.